PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROJECT BASED LEARNING PADA MATERI PEMISAHAN CAMPURAN - Apriliantika, Apriliantika; Muharini, Rini; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to produce LKPD project based learning that was feasible to use and to measure the response of teachers and students to the products developed. The research used was R&D referring to the Kemp model. The sampling technique used was purposive sampling. The initial development trial subjects consisted of 15 people, the main trial consisted of 30 people and the trial of the use of the product consisted of 13 students of grade VII in SMPN 12 Pontianak and 3 natural science teachers. Data collection tools used were the feasibility assessment sheet and the questionnaire responses of teachers and students. The results of the feasibility assessment conducted by experts gave a very decent level of eligibility, namely the content, presentation, language, and graphic viability with percentages respectively 87.3%, 84.1%, 95.3%, and 96.6 %. The product trial results showed the students' response with an average score of 88.03% and the teacher's response with an average score of 98.3%, which classified as a high category. The effectiveness of LKPD can be seen from the results of the students' skills in making filtration equipment which was 87.8 and distillation equipment which was 84.8 with high criteria.Â Keywords: Mixed Separation, Project Based Learning, Worksheet Â